Increasing value and reducing waste in stroke research - Berge, Eivind; Al-Shahi Salman, Rustam; van der Worp, H. Bart; Stapf, Christian; Sandercock, Peter; Sprigg, Nikola; Macleod, Malcolm R.; Kelly, Peter J.; Nederkoorn, Paul J.; Ford, Gary A. (Elsevier, 2017)
Stroke represents a major burden to patients and society, and resources spent on stroke research must be used efficiently and produce good value in terms of improvements in human health. However, there are many examples of poor value from stroke research funding, which result from the way in which stroke research has been chosen, designed, conducted, analysed, regulated, managed, disseminated, or reported. In a project including a survey and a symposium and involving stroke researchers in the European Stroke Organisation we have sought to identify sources of inefficiency and waste, recommended approaches to increase value, and highlighted examples of best practice in stroke research. Recent evidence suggests that progress has been made, but there is room for much improvement, and stroke researchers, funders and other stakeholders might consider our recommendations when planning new research.